2023
DOI: 10.1002/sscp.202300156
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study: Fragmentation patterns of flavonoid‐C‐glycosides in the enriched flavonoids from corn silk using high‐efficiency ultra‐high‐performance liquid chromatography combined with quadrupole time‐of‐flight mass spectrometry

Yumei Wang,
Meiling Gu,
Jialin Mao
et al.

Abstract: Flavonoid‐C‐glycosides with various pharmacological actions were abundant in corn silk, and fragmentation in mass spectra of flavonoid‐C‐glycosides compounds was particularly important. This paper aimed to supervise the fragmentation patterns of flavonoid‐C‐glycosides in the enriched flavonoids from corn silk by high‐efficiency ultra‐high‐performance liquid chromatography combined with a quadrupole time‐of‐flight mass spectrometry approach. Therefore, the flavonoids were extracted by heating reflux and then pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Among them, apigenin, luteolin, robinin, and chrysoeriol are the common mother nucleus structures. Our previous study showed that 35 flavonoid constituents were successfully identified in the enrichment of corn silk using the LC-MS/MS approach; luteolin-C-glycosides and apigenin-C-glycosides account for 40% of the total and play a critical role [16]. Yi Ting et al [17] used HPLC-Q-TOF-MS technology to analyze the total flavonoids of corn silk prepared by reflux extraction and macroporous resin enrichment; as a result, 19 flavonoids-10 flavonoid glycosides and 9 flavonols were identified.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Among them, apigenin, luteolin, robinin, and chrysoeriol are the common mother nucleus structures. Our previous study showed that 35 flavonoid constituents were successfully identified in the enrichment of corn silk using the LC-MS/MS approach; luteolin-C-glycosides and apigenin-C-glycosides account for 40% of the total and play a critical role [16]. Yi Ting et al [17] used HPLC-Q-TOF-MS technology to analyze the total flavonoids of corn silk prepared by reflux extraction and macroporous resin enrichment; as a result, 19 flavonoids-10 flavonoid glycosides and 9 flavonols were identified.…”
Section: Flavonoidsmentioning
confidence: 99%